Peningkatan Kesadaran Hukum Kesehatan berdasarkan UU No. 17 Tahun 2023 bagi Perawat di Rumah Sakit Umum Melati Perbaungan sebagai Upaya Pencegahan Malpraktik - Emirza Henderlan Harahap (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Legal awareness among nurses is crucial to prevent malpractice that negatively impacts patients and healthcare institutions. This community service project aimed to enhance nurses’ understanding of health law based on Law No. 17 of 2023 at Melati General Hospital Perbaungan. The method employed was participatory interactive training and group discussions conducted over three months. The results indicated a significant improvement in nurses’ legal knowledge and a positive shift in their compliance behavior in daily practice. The program also fostered the emergence of local leaders who actively educate peers and contribute to creating a legal-conscious work culture. These findings suggest that targeted legal education can effectively reduce malpractice risks and improve healthcare quality.